(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study investigated the effect of nutrient media supplemented with BERES UNIVERSAL fertilizer and the phytohormone IAA1 on accelerating and enhancing the efficiency of root formation in Capparis spinosa L. regenerants.